2017
DOI: 10.1101/155457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclease escape elements protect messenger RNA against cleavage by multiple viral endonucleases

Abstract: During lytic Kaposi's sarcoma-associated herpesvirus (KSHV) infection, the viral endonuclease SOX promotes widespread degradation of cytoplasmic messenger RNA (mRNA). However, select mRNAs, including the transcript encoding interleukin-6 (IL-6), escape SOX-induced cleavage. IL-6 escape is mediated through a 3' UTR RNA regulatory element that overrides the SOX targeting mechanism. Here, we reveal that this protective RNA element functions to broadly restrict cleavage by a range of homologous and non-homologous … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…Recently, Mendez et al demonstrated that SOX cleaves its target mRNA without other factors by in vitro cleavage assay [22]. Moreover, Muller et al revealed that some mRNAs that 'overrided' SOX were also degraded, suggesting multiple viral endonucleases' existence [23]. BGLF5 in EpsteineBarr virus (EBV) plays a role in processing non-linear or branched viral DNA intermediates in order to promote the production of mature packaged unitlength linear progeny viral DNA molecules [24], serves as an endoribonuclease of host mRNA after infection [25].…”
Section: Virus/bacteriophage Induces Host Rna Degradationmentioning
confidence: 99%
“…Recently, Mendez et al demonstrated that SOX cleaves its target mRNA without other factors by in vitro cleavage assay [22]. Moreover, Muller et al revealed that some mRNAs that 'overrided' SOX were also degraded, suggesting multiple viral endonucleases' existence [23]. BGLF5 in EpsteineBarr virus (EBV) plays a role in processing non-linear or branched viral DNA intermediates in order to promote the production of mature packaged unitlength linear progeny viral DNA molecules [24], serves as an endoribonuclease of host mRNA after infection [25].…”
Section: Virus/bacteriophage Induces Host Rna Degradationmentioning
confidence: 99%
“…These include lack of a targeting motif, indirect transcriptional effects, and active evasion of ribonucleolytic cleavage (16,20-24). This latter phenotype, termed “dominant escape”, is particularly notable as it involves a specific RNA element whose presence in the 3’ UTR of an mRNA protects against SOX cleavage, regardless of whether the RNA contains a targeting motif (19-21). This protective RNA element was termed SRE (for S OX R esistance E lement), but we recently showed that the SRE is also effective against a broad range of viral endonucleases.…”
Section: Introductionmentioning
confidence: 99%
“…This protective RNA element was termed SRE (for S OX R esistance E lement), but we recently showed that the SRE is also effective against a broad range of viral endonucleases. Perhaps more surprisingly, the SRE is unable to restrict endonucleolytic cleavage originating from a cellular endonuclease, making it the first identified viral-specific ribonuclease escape element(19). We showed that this broad-acting RNA element is not characterized by a defined sequence motif (19) rendering it difficult to identify new escaping transcripts by traditional sequence search.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations